Recast type, repair, and acquisition in AAC mediated interaction. Issue 1 (16th January 2020) - SOTO, Gloria; CLARKE, Michael T.; NELSON, Keith; STAROWICZ, Renee; SAVALDI-HARUSSI, Gat
Abstract: The present study investigated the effects of different types of recasts and prompts on the rate of repair and spontaneous use of novel vocabulary by eight children with severe motor speech disabilities who used speech-generating technologies to communicate. Data came from 60 transcripts of clinical sessions that were part of a conversation-based intervention designed to teach them pronouns, verbs, and verb inflections. The results showed that, when presented alone, interrogative choice and declarative recasts led to the highest rates of child repair. The results also showed that when children were presented with recasts and prompts to repair, the rate of repair increased. Spontaneous use of linguistic targets was significantly and positively related to conversational sequences where the adult recast was followed by child repair. These findings suggest that using different recast types and prompts to repair may be beneficial for spontaneous use of linguistic targets in this population.